Smoke derived taint in grapes and wine - Kennison, Kristen Renee (Curtin University, 2011)
Smoke derived taint in grapes and wine is an issue of increasing significance and severity for the wine industry internationally. On commencement of this research, insufficient knowledge existed as to the effects of smoke on grapevines and the development of smoke taint in wine, with no substantial published information. This research was undertaken to investigate the effect of smoke exposure to grapevines on the development of smoke aromas, flavours and compounds in final wines. As such, this study pioneers the purposeful application of smoke to grape bunches and field-grown grapevines to establish the direct link between smoke exposure and the development of smoke taint in wine.This research identified key periods of grapevine sensitivity to smoke uptake as: (1) from shoots 10 cm in length to full-bloom (low levels of smoke taint); (2) from berries pea size to the onset of veraison (variable levels of smoke taint); and (3) from 7 days post veraison to harvest (high levels of smoke taint). A novel smoke application methodology consisting of a smoke generator and greenhouse-grade tent was developed to facilitate the accurate application of smoke treatments to field-grown grapevines. Smoke treatments were applied to grapevines at key stages during the seasonal growth cycle, on repeated occasions and at a range of densities and durations.Elevated concentrations of guaiacol, 4-methylguaiacol, 4-ethylguaiacol, 4-ethylphenol, eugenol and furfural were detected, by gas chromatography-mass spectrometry analysis, in wines made from fruit exposed to smoke; whereas these compounds were either not detected or detected in trace concentrations in wines produced from unsmoked (control) fruit. Wine sensory analysis established a difference between smoked and unsmoked wines, with smoked wines exhibiting ‘smoky’, ‘dirty’, ‘earthy’, ‘burnt’ and ‘smoked meat’ aromas. The density and duration of smoke exposure to grapevines was found to affect the chemical composition and sensory properties of wine and repeated smoke applications demonstrated a cumulative effect.